Opportunities and Challenges in Implementing Circular Economy within Digital Platforms - Nolan Liam; Arthur Simanjuntak; Henry Newell; Tan, Wei Xiang (International Transactions on Education Technology (ITEE), 2025)
The rapid advancement of digital platforms has opened new avenues for integrating circular economy practices, particularly in optimizing resource use, reducing waste, and fostering sustainable growth. This study aims to investigate both the opportunities and challenges that organizations encounter when implementing circular economy principles within digital environments, focusing on how these platforms can drive more sustainable operations. Adopting a mixed-methods approach, the research gathers quantitative data from digital platform users through surveys and qualitative insights from in-depth interviews with industry experts and business owners across various sectors. The findings indicate that digital platforms present significant opportunities for enhancing resource efficiency, promoting product life extension through recycling and reuse options, and enabling collaborative networks that support circular practices. However, substantial challenges are identified, including high initial investment costs, technical and regulatory barriers, and a lack of widespread digital literacy, especially among small and medium-sized enterprises. Additionally, the research highlights issues related to data privacy and technological compatibility, which can limit broader adoption and effective implementation of circular strategies. The study concludes that while digital platforms hold transformative potential for advancing circular economy goals, success depends on developing supportive policies, fostering collaborative ecosystems, and enhancing digital skills across industries to overcome these obstacles. This research provides valuable insights for policymakers, business leaders, and technology providers seeking to leverage digital tools in the shift toward a sustainable circular economy.